PENGARUH KONDISI LINGKUNGAN KELUARGA TERHADAP SIKAP SALING MENGHARGAI DAN KEDISIPLINAN SISWA DALAM MENERAPKAN NORMA DAN ATURAN PADA SISWA KELAS IV SD N PENDRIKAN KIDUL KOTA SEMARANG - Nadia Bintang Karyadi; Zahra Nabila Permatahati; Abdillah Ramdani Chadiatno; Vanyadifa Brillianesti Zamzami; Irfan Adhi Nugroho; Lilis Wuri Listriyani; Nur Indah Wahyuni (STKIP Subang, 2025)
This study investigates the essential role of the family environment in shaping children’s character, particularly regarding respect and discipline among fourth-grade students at SDN Pendrikan Kidul. The problem identified in the classroom shows that several students still display disrespectful behaviors, such as teasing peers and interrupting conversations, as well as low discipline, including late submission of assignments and violations of class rules. These conditions indicate a significant influence of family dynamics and parenting styles. The purpose of this study is to analyze how the family environment and parenting patterns affect students’ respectful attitudes and discipline. Using a descriptive qualitative method, data were collected through observations in Grade IV A and IV B and semi-structured interviews with homeroom teachers. The findings reveal that students from harmonious families with democratic parenting tend to demonstrate better social skills, stronger discipline, and higher self-control, supported by warm, affectionate, and consistent interactions at home. In contrast, students from non-intact families or those receiving inconsistent supervision and limited parental attention often show disrespectful behavior, low empathy, and frequent rule violations. The study concludes that a supportive family environment and consistent parenting play a crucial role in developing children’s character and self-regulation, whereas lack of guidance contributes to social difficulties and disciplinary problems. The implications highlight the critical role of teachers in strengthening character development for students who receive limited support at home and recommend improved communication and supervision from parents, along with enhanced collaboration between teachers and schools to foster students’ social-emotional growth.